Hydrogen storage in carbon materials—A review. Issue 2 (13th May 2019) - Mohan, Man; Sharma, Vinod Kumar; Kumar, E. Anil; Gayathri, V.
Abstract: It is well known that three challenges of hydrogen economy, that is, production, storage, and transportation or application put tremendous stress on scientific community for the past several decades. Based on several investigations, reported in literature, it is observed that the storage of hydrogen in solid form is more suitable option to overcome the challenges like its storage and transportation. In this form, hydrogen can be stored by absorption (metal hydrides and complex hydrides) and adsorption (carbon materials). Compared to absorption, adsorption of hydrogen on carbon materials is observed to be more favorable in terms of storage capacity. Taking in to account of these facts, in this short review, an overview on hydrogen adsorption on activated carbon and different allotropes of carbon like graphite, carbon nanotubes, and carbon nanofibers is presented. Synthesis processes of all the carbon materials are discussed in brief along with their hydrogen storage capacities at different operating conditions, and thermodynamic properties and reaction kinetics. In addition, different methods to improve hydrogen storage capacities of carbon materials are presented in detail. Finally, comparison is made between different carbon materials to estimate the amount of hydrogen that can be stored and retract practically. The experimentally measured maximum hydrogen storage capacity of activate carbon, graphite, single‐walled nanotubes, multiwalled nanotubes, and carbon nanofibers at room temperature are 5.5 wt%, 4.48 wt%, 4.5 wt%, 6.3 wt%, and 6.5 wt%, respectively. Abstract : An overview on hydrogen adsorption on activated carbon and different allotropes of carbon like graphite, carbon nanotubes, and carbon nanofibers is presented. Different carbon materials suitable for hydrogen storage are discussed in detail; it is synthesis process, hydrogen storage capacity and methods to improve storage capacity, thermodynamic properties, and reaction kinetics. Hydrogen storage capacities of different carbon materials are compared to estimate the amount of hydrogen that can be stored and retract practically at room temperature and pressure. The maximum hydrogen storage capacity of activate carbon, graphite, single‐walled nanotubes, multiwalled nanotubes, and carbon nanofibers at room temperature are 5.5 wt%, 4.48 wt%, 4.5 wt%, 6.3 wt%, and 6.5 wt%, respectively.